Epidemiological insights into sexually transmitted infections and pregnancies among gender-based violence victims in the Northern province of Rwanda: Findings from the Isange One-stop Center at Ruhengeri Referral Hospital - UWUMUREMYI, Fabrice; Dusengimana, Violette; Twambazimana, Gabriel; Mpinganzima, Lydivine; USENGIMANA, Angelique; Nshuti Shema, David; TUYISHIMIRE, Norbert; Bisanukuri, Evergiste; Nsanzabaganwa, Christian; HABYARIMANA, Thierry (Journal of Drug Delivery and Therapeutics, 2025)
Introduction: Gender-based violence (GBV) is violence directed against a person because of their gender. Both women and men experience gender-based violence, but the majority of victims are women and girls. Sexually transmitted infections (STIs) are infections that are transmitted from one person to another through sexual contact. There is evidence that GBV increases the risk of STIs and pregnancy. The objective of this study was to determine the prevalence of STIs and pregnancy among GBV patients attending the Isange One Stop Center at Ruhengeri Referral Hospital.Methodology: This retrospective study involved the consultation of archived data and recorded data in files for all GBV cases received from January to December 2021. The victim’s information, such as laboratory findings, residential sector information, demographic characteristics, and months in which GBV cases were recorded. The Statistical Package for the Social Sciences (SPSS) version 20 was used for data analysis.Results: A total of 308 GBV cases were reported, 93.8% of which involved females. Most victims (46.4%) were adolescents aged 11–20 years. Urban areas, particularly the Muhoza (26%) and Cyuve (22.1%) sectors, reported the highest number of cases. The prevalence of STIs among GBV victims was 68.5%, with trichomoniasis (18.2%) and gonorrhoea (14.6%) being the most common infections. Hepatitis B and syphilis were identified in 6.2% and 5.2% of the patients, respectively.Conclusion: Although efforts are being made in Rwanda to fight against GBV, the number of GBV cases is continually increasing, with the incidence of STIs and undesirable pregnancies increasing, especially among young adolescents. Therefore, additional focus and efforts are needed to lower this rate of GBV among young adolescents. Preventive measures should be improved to eliminate GBV cases and subsequent effects.Keywords: Gender, Sexual violence, intimate partner violence, STIs, pregnancy.